A case report: septic shock due to (tropical) pyomyositis and multiple metastatic embolisms caused by Panton Valentine Leukocidin-positive methicillin-sensitive staphylococcus aureus in a 12-year-old boy. Issue 2 (4th March 2022) - Vanbiervliet, Valérie; Demeyer, Ignace; Claus, Filip; Van Vaerenbergh, Kristien
ABSTRACT: Case Report: A 12-year-old boy, of Congolese roots and without medical history, first presented to our Emergency Department 3 days after blunt trauma of the left ankle. The boy represented on two more occasions in the next 3 days due to ongoing pain. On the last occasion he presented with severe hypoglycaemia. He was diagnosed with severe septic shock, secondary to subperiosteal abscess formation / osteomyelitis of the ankle. The patient was transferred to the paediatric intensive care unit where appropriate medical care was provided, including broad-spectrum antibiotic therapy, high dose vasopressor / inotropic support, surgical debridement of abscesses and below-knee amputation. Panton Valentine Leukocidin Toxin and Pyomyositis Tropicalis: The causative organism was a methicillin-susceptible S. aureus, which upon further identification was a carrier of the PVL (Panton Valentine leukocidin) toxin. This pathogen is responsible for severe musculoskeletal infections. In children these infections are often associated with more severe clinical course requiring a higher need for surgical intervention and longer hospital stay.Tropical pyomyositis is a disease caused by Staphylococcus aureus, often seen in tropical countries, and classically presented with muscle abscesses. Young males between the ages of 10-40 years old are the most susceptible, and often present with a history of blunt trauma. Treatment generally requires a combination of an anti-staphylococcal agent, and an anti-toxic agent blocking bacterial protein-synthesis of PVL. Source control by surgical debridement also plays a major role in the treatment of PVL-infection. Despite agressive treatment, mortality still varies from 0.5% to 2%.